Adaptive Leadership and Institutional Development in Islamic Education: A Case Study of Madrasah Diniyah At-Ta’abud Wonokromo - In, Khurun; Dasuki, Qurrotul A’ Yuni; Nurwahid, Arif (Journal of Islamic Education Management Research, 2024)
Purpose – This study investigates the adaptive leadership model at Madrasah Diniyah At-Ta’abud to understand its role in strengthening organizational structures, enhancing curriculum development, improving internal communication, and fostering student potential in a pesantren-based Islamic education context. Design/methods – A qualitative descriptive approach was employed, using observations, structured and unstructured interviews, and document analysis. Data were analyzed inductively through condensation, display, and conclusion verification, with triangulation applied to ensure validity and reliability. Findings – The leadership approach successfully integrated traditional Islamic values with modern administrative practices, resulting in a clarified organizational hierarchy, dynamic curriculum reforms, participatory governance, and innovative student admissions systems. Challenges identified include difficulties in internal team coordination and inconsistency in digital communication responsiveness. Research implications/limitations – Limitations stem from reliance on a single case study setting, affecting the generalizability of findings; additionally, the varied responsiveness to digital coordination tools among staff presented unforeseen interpretive challenges. Practical implications – This study underscores the necessity of adaptive, inclusive, and technologically literate leadership models to sustain and advance the relevance of Islamic educational institutions in contemporary contexts. Findings suggest that similar institutions can benefit from blending traditional and modern strategies in governance and administration. Originality/value – By providing a detailed analysis of adaptive leadership practices in an under-researched Islamic education setting, this study offers new insights for leadership development, institutional resilience, and educational reform within the pesantren system and beyond.